Circadian Rest and Activity Rhythms and Cognitive Change in the Baltimore Longitudinal Study of Aging. (17th December 2021) - Rabinowitz, Jill; An, Yang; Wanigatunga, Sarah; Zipunnikov, Vadim; Wu, Mark; Simonsick, Eleanor; Resnick, Susan; Spira, Adam
Abstract: Alterations in 24-hour movement patterns, or circadian rest/activity rhythms (RARs), commonly occur with aging. Using linear mixed effects (LME) modeling, we examined associations of baseline RARs with longitudinal change in cognition. Participants (N=424; 47% male, baseline age 72.8±10.1 years) were from the Baltimore Longitudinal Study of Aging and completed 5.6±0.8 nights of wrist actigraphy at baseline. Tests of memory, executive function, attention, language, and visuospatial ability were administered at baseline and subsequent visits (3.7±1.7 years of follow-up in those with >1 visit (n=295)). In unadjusted random intercept and slope LME models, greater RAR stability predicted slower memory decline, and higher activity during participants' least active 5 hours (L5) predicted slower decline in visuospatial ability. After covariate adjustment, higher activity in participants' most active 10 hours (M10) and higher L5 predicted slower decline in visuospatial ability (p<.05). Further research is needed on RARs as risk factors for later-life cognitive decline.